Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fmed.2022.1007892
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of IgE in patients with psoriasis: Is it a paradoxical phenomenon?

Abstract: Immunoglobulin E (IgE) elevation is a hallmark of allergic conditions such as atopic dermatitis (AD). The pathogenesis of AD is typically associated with high levels of IL-4 and IL-13 produced by activated T helper 2 (Th2) cells. Psoriasis, on the other hand, is an inflammatory skin disease mainly driven by Th17 cells and their related cytokines. Although the immunopathologic reactions and clinical manifestations are often easily distinguished in the two skin conditions, patients with psoriasis may sometimes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 192 publications
(207 reference statements)
0
6
0
Order By: Relevance
“…Hypersensitivity reaction I begins with Th2, which will stimulate the differentiation of B cells into plasma cells, producing IgE. Furthermore, a cross-reaction occurs among basophils, mast cells, and IgE, making basophils release inflammatory mediators chemotactic for eosinophils (Shi et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Hypersensitivity reaction I begins with Th2, which will stimulate the differentiation of B cells into plasma cells, producing IgE. Furthermore, a cross-reaction occurs among basophils, mast cells, and IgE, making basophils release inflammatory mediators chemotactic for eosinophils (Shi et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, our results with the STAT6 inhibitor were insufficient to show an indispensable role for Th2 responses, including IL-4/IL-13 and IgE/IgG1 in imiquimod-induced and OVA-exacerbated psoriasis, although Th2 responses are thought to participate in psoriasis development. 5) The beneficial potential of the STAT6 inhibitor on imiquimod-induced psoriasis should be examined in more detail, and, in turn, the importance of the role of Th2 in human psoriasis may become an attractive research focus.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 99%
“…4) Additionally, the Th2 response is expected to be implicated in psoriasis. 5) However, the relationship between the two diseases remains controversial. Dai et al 6) revealed that the presence of each disease increases the risk of the other, but Kirsten et al 7) found that the prevalence of atopic diseases was lower in patients with psoriasis than in those without.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cytokines contribute to inflammation and exacerbation of atopic lesions . Indeed, atopic patients exhibit higher levels of immunoglobulins E (IgE), which is overproduced as a consequence of inflammatory response and contributes to the prolongation of atopic lesions . Furthermore, the genetic alterations in cell-mediated immune responses lead to disruption of the stratum corneum (SC), the outermost layer of skin .…”
Section: Introductionmentioning
confidence: 99%